2007
DOI: 10.1002/ange.200605207
|View full text |Cite
|
Sign up to set email alerts
|

Phloroglucinolderivate Guttiferon G, Aristoforin und Hyperforin: Inhibitoren der menschlichen Sirtuine SIRT1 und SIRT2

Abstract: Die Naturstoffe Guttiferon G und Hyperforin (1) sowie das synthetische Aristoforin (2) sind Inhibitoren der menschlichen Sirtuine SIRT1 und SIRT2. Zudem sind Guttiferon G und 2 weniger toxisch sowie stärkere Inhibitoren der Zellproliferation als 1. Diese Verbindungen können wertvoll für die Epigenetik sowie zur Aufklärung der Rolle von Sirtuinen bei Krebs, Alterungsprozessen, neurodegenerativen Erkrankungen, Adipositas oder Diabetes sein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
9
0
2
Order By: Relevance
“…[210] In addition to other important bioactivies, [211] 229 was shown to induce promising neurological effects. For example, the antidepressant activity of 229 was attributed to its ability to inhibit neuronal uptake of various neurotransmitters.…”
Section: Neurotrophic Natural Productsmentioning
confidence: 99%
“…[210] In addition to other important bioactivies, [211] 229 was shown to induce promising neurological effects. For example, the antidepressant activity of 229 was attributed to its ability to inhibit neuronal uptake of various neurotransmitters.…”
Section: Neurotrophic Natural Productsmentioning
confidence: 99%
“…[5] Further Sirt2 inhibitors have been discovered through a virtual screening approach, but cellular activity and verification of protein hyperacetylation have not been demonstrated. [15][16][17] The sirtuin inhibitor cambinol (3) was discovered from random screening, and for the first time anticancer activity in an animal model could be demonstrated with this compound. [18] Lately, indoles such as 4, with activity down to~0.1 mm have been presented.…”
Section: Introductionmentioning
confidence: 99%
“…Some compounds appear to be rather promising with IC 50 values close to 1 mmol L À1 (or even lower), which is a concentration that might well be achieved as a systemically relevant therapeutic dose. [6][7][8][9][10] Many others, however, exhibit IC 50 values that are clearly higher than 10 mmol L À1 and, in some instances, even approach the millimolar range. [11][12][13][14] In the present study a group of seven indoloquinolizidine derivatives was identified on the basis of functional screening of approximately 11 000 natural-product derived and inspired compounds, which with IC 50 values close to 2 mmol L À1 , inhibited proliferation in different cell lines and increased the amount of apoptotic cells by up to 600 % as compared to the control value.…”
Section: Introductionmentioning
confidence: 99%